An Argument for Expanding the Role of Pediatric Decision-Making and Preference in Child Abuse/Neglect Assessments and Plan - Rissa Fedora; Becky Li (Case Reports in Psychiatry)
Child maltreatment can have long-term sequelae and thus requires appropriate interventions. In the United States, reports of suspected child maltreatment are primarily handled by the Child Protective Services (CPS). We present a case of a 12-year-old female who was involuntarily hospitalized for suicidal ideation after CPS responded to a report of her abuse by her mother. Despite continuously expressing fear of her mother and pleading to not be discharged home, CPS ultimately determined that the child was safe to return home to her abuser. The child’s subsequent loss to follow-up puts the child’s safety and long-term well-being into question. In this article, we discuss the current protocol of CPS reporting, investigation, and outcome. We also explore the roles of pediatric decision-making and forensic or custody evaluation when maltreatment is apparent.